Pemodelan Underpass Tahan Banjir Menggunakan Software 3DS Max - Febri Auditia; Yuyun Dwi Lestari; Arif Budiman (UIN Sumatera Utara, 2022)
The problem in this study is how to model a flood-resistant underpass with a 3-dimensional model using 3DS Max software to make it look more attractive. In this study, the author uses the reference for the Ngurah Rai Intersection underpass in Bali Province as an example of the design that the author will make. The research objective is to implement the modeling of an underpass that can withstand flooding with a 3-dimensional model into 3DS Max software with very effective and maximum functions. One way to overcome this problem is to take advantage of the development of information and communication technology that exists at this time by using the 3DS Max application which can create a simulation in the form of animation. In doing the modeling of the 3D animation flood-resistant underpass design, the author uses 2 (two) software, namely 3DS Max and Wondershare Filmora, the 3DS Max software functions for the modeling process, gives textures and makes animation, while the Wondershare Filmora software is used for the animation editing process that has been designed. and made into a video and giving sound so as to produce a very interesting animated display. Making 3D animation is done in three stages, namely modeling, texturing, animation and rendering. Completion of the research process in the flood-resistant underpass modeling process requires ideas and creativity so that a flood-resistant underpass that is designed looks attractive and looks comfortable for motorists to pass, the design of a 3D animation-based flood-resistant underpass was created using 3DS Max software and Wondershare software. Filmora. Keywords: Animation, 3D Modeling, Flood Resistant Underpass